2019
DOI: 10.1111/ijfs.14296
|View full text |Cite
|
Sign up to set email alerts
|

Development of vitamin E‐enriched functional foods: stability of tocotrienols in food systems

Abstract: Summary Tocotrienols are members of the vitamin E family that provide many nutritional benefits. Developing tocotrienol‐fortified functional foods introduces vitamin E into consumers diets without changing their food habits. The purpose of this study was to compare the stability of tocotrienols in bulk form and six food matrices at a fixed dose (40 mg kg−1) under accelerated and conventional storage conditions. The delta‐ and gamma‐tocotrienol content was measured using HPLC, and the sensory attributes were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“… [18] recorded that the ROB activity was significantly higher in the vitamin-C group than the probiotic fed L. rohita . Likewise, the stimulation of ROB activity after dietary probiotic supplementation involving other feeding regimes and feeding durations have been previously reported in various fish [ 19 , 49 ] or diets containing vitamin-E and other immunostimulants [ 46 , 34 , 50 ]. Upon A. hydrophila challenge, a significant reduction in ROB activities was recorded in all groups on 6-hpi and 7-dpi.…”
Section: Discussionmentioning
confidence: 80%
“… [18] recorded that the ROB activity was significantly higher in the vitamin-C group than the probiotic fed L. rohita . Likewise, the stimulation of ROB activity after dietary probiotic supplementation involving other feeding regimes and feeding durations have been previously reported in various fish [ 19 , 49 ] or diets containing vitamin-E and other immunostimulants [ 46 , 34 , 50 ]. Upon A. hydrophila challenge, a significant reduction in ROB activities was recorded in all groups on 6-hpi and 7-dpi.…”
Section: Discussionmentioning
confidence: 80%
“…For human nutrition, diet is the major source of tocol intake. Especially when compared with animal-derived foods, edible plant-derived products are the major source of tocols, such as oil seeds; green parts of plants; whole grains; nuts; and vegetable oils of wheat germen, sunflower, corn, as well as olives [2,[13][14][15][16]. Vegetable oils, quintessential lipid foods in the human diet, are considered very suitable for the enrichment of tocopherols due to the lipophilicity of tocopherols [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported that the s-SEDDS has improved stability over time compared to conventional liquid SEDDS [77,78]. From the literature, only a small number of solid tocotrienol products are available in the market and were used in studies, with no specific indication of them being an s-SEDDS preparation [79][80][81]. The stability of tocotrienols is reportedly affected by several environmental factors including rates of lipid oxidation in the matrix, types and concentration of tocopherols, and the presence of other minor compounds such as free fatty acids, water, and minerals [82].…”
Section: Characterisation Of the Optimised S-seddsmentioning
confidence: 99%